Contemporary friendships and social vulnerability among youth: Understanding the role of online and offline contexts of interaction in friendship quality. (December 2021) - Scott, Riley A.; Stuart, Jaimee; Barber, Bonnie L.
The prevalence of internet-connected devices in everyday life means that social interactions now frequently take place online. However, for socially vulnerable youth, it may be particularly important to examine distinctions between online and offline contexts of friendships. The current study sought to increase understanding of friendships in the digital era by exploring the associations of social anxiety and loneliness with frequency of interactions with friends, and in turn, friendship quality, as moderated by primary context of interaction with friends (online, offline, or equally online and offline). A sample of Australian young adults ( N = 658; 59.8% female; M age = 19.41, SD = 2.04) who reported having friendships conducted across both online and offline contexts were included in the study. A serial mediation model tested the effects of social anxiety on perceptions of friendship quality, through loneliness and frequency of interacting with friends. The findings suggest that social vulnerabilities are negatively associated with friendship quality for young adults who primarily interact with friends offline or both online and offline. However, among those who primarily interact with friends online, social vulnerabilities are not significantly associated with friendship quality. These results provide insight into contemporary friendships and highlight how social vulnerabilities are associated with perceptions of friendship quality across online and offline settings.